Otimização de extração por ultrassom e micro-ondas de compostos fenólicos das folhas de Lippia alba (Mill.) N. E. Brown e Lantana camara Linn. - Jesus, Raphael Amancio de (2022)
In this work, extraction optimization was performed by two techniques, ultrasound (UAE) and microwave (MAE), to obtain, simultaneously, extracts with better results in yield and total phenolic content, from Lippia alba and Lantana camara leaves, separately, using a Box-Behnken design and response surface methodology (RSM). The extracts of L. alba obtained under the optimum conditions by UAE (29% ethanol, 17.8 min and solvent to solid ratio of 71 mL/g) and MAE (43% ethanol, 15 min and microwave power of 600 W) resulted in yields of 20.33 and 26.94% and TPC of 30.86 and 41.13 mg EAG/g ms, respectively. Considering the species L. camara, the extracts obtained under the optimum conditions by UAE (35% ethanol, 25 min and solvent to solid ratio of 60:1 mL/g) and MAE (53% ethanol, 15 min and microwave power of 300 W) provided yields of 32.50 and 38.61% and TPC of 102.89 and 109.83 mg EAG/g ms, respectively. The extracts obtained by MAE from each species showed higher extraction yields, total phenolic content (TPC), total flavonoid content (TFC) and antioxidant activities (DPPH, ABTS and FRAP) in relation to their respective conventional extracts (maceration, infusion, decoction and Soxhlet), highlighting the highest results presented by the species L. camara. The extracts obtained by UAE from each species showed higher values of TPC, TFC and antioxidant activities in relation to their respective maceration and infusion extracts. However, the extracts obtained from both species showed low cytotoxic activities against tumor cells and low enzymatic inhibition activities (AChE and BChE), indicating the need for further studies to evaluate their real biological potentials in relation to these activities. Through the analysis by Liquid Chromatography coupled to a Diode Array detector, it was possible to verify the presence of iridoids, phenolic acids, phenylpropanoids and flavonoids in the extracts of L. alba and L. camara, which corroborates the high antioxidant activities presented by the extracts of these species.